An update on the short-term impacts of COVID-19 on the Malawian economy, 2020–2021 - Baulch, Bob; Botha, Rosemary; Pauw, Karl (International Food Policy Research Institute, 2021)
This report provides an update on the short-term impacts of COVID-19 on the Malawian economy in light of the sharp increase in COVID-19 cases in December 2020 and January 2021. It extends and updates the results of previous SAM multiplier-based modeling undertaken by IFPRI during 2020 with a particular focus on the impacts of COVID-19 control measures on the recovery of the Malawian economy in 2021. As before, we also consider the short-run effects of external shocks associated with disruptions in trade and tourism, foreign direct investment, and remittance flows on the Malawian economy, as well as two medium-term paths assuming either faster or slower easing of restrictions during the remainder of 2020 and 2021.